26.4k views
5 votes
–19y − 6y + 17y − –14 = –18

y=?

User Jkpieterse
by
5.2k points

2 Answers

2 votes

Answer:


y=(16)/(9)

Step-by-step explanation:

Given: –19y − 6y + 17y − –14 = –18

We have to isolate the variable (y) to get it by itself. Firstly, we'll get rid of the double negative.

–19y − 6y + 17y − –14 = –18

Subtracting a negative number by a negative number automatically means it's an addition sign.

–19y − 6y + 17y + 14 = –18

Now, let's add our common variables.

We have three.

–19y − 6y + 17y + 14 = –18

We get:

-18y + 14 = -18

The fourteen does not belong with the variable, so we'll move it to the other side. To do this, we'll subtract the fourteen on both sides of the equation.

-18y + 14 = -18

-14 -14

Now we have:

-18y = -32

The last step is to divide. In doing so, the quotient is:


y=(16)/(9)

User Havoc P
by
5.0k points
1 vote

Answer: y=4

Step-by-step explanation: first simplify the equation and then take off numbers equally from both sides

User Max Conway
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.